2016
DOI: 10.5935/0103-5053.20160114
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Determination of Sulfonamides with a Modified Glassy Carbon Electrode Using Carboxyl Multiwalled Carbon Nanotubes

Abstract: New glassy carbon electrode (GCE) modified with carboxyl multiwalled carbon nanotubes (MWCNTs) and treated with ultrasonic dispersing in N,N-dimethylfomamide (DMF) media, namely DMF/carboxyl/MWCNTs/GCE, was prepared for electrochemical determination of sulfonamides (SAs). Electrochemical behavior of SAs based on DMF/carboxyl/MWCNTs/GCE was investigated by cyclic voltammetry and impedance spectroscopy. The effects of various experimental parameters on the response of electrode such as pH of buffer, scan rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…2,3 These are used for the treatment of bacterial and fungal infections. 4 SMZ and SDZ are also widely used in veterinary medicine to promote growth in animal feed and play major roles in livestock, aquaculture, and pharmaceutical industries. 5−7 These, along with some of their metabolites, are among the most commonly used antibiotics that have been detected in wastewaters.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 These are used for the treatment of bacterial and fungal infections. 4 SMZ and SDZ are also widely used in veterinary medicine to promote growth in animal feed and play major roles in livestock, aquaculture, and pharmaceutical industries. 5−7 These, along with some of their metabolites, are among the most commonly used antibiotics that have been detected in wastewaters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sulfamethazine (SMZ) and sulfadiazine (SDZ) are sulfonamide antibiotics having extensive antibacterial activities . The structure of SNs contains −SO 2 NH 2 or −SO 2 NH– groups with distinct five- or six-membered heterocyclic rings; there are presently many derivatives under the same group of drugs, while some are newly emerging. , These are used for the treatment of bacterial and fungal infections . SMZ and SDZ are also widely used in veterinary medicine to promote growth in animal feed and play major roles in livestock, aquaculture, and pharmaceutical industries. These, along with some of their metabolites, are among the most commonly used antibiotics that have been detected in wastewaters. , Bacterial resistance and toxicity of these drugs can cause a genuinely negative impact on human well-being and the environment. Sulfamethazine (Figure A) and sulfadiazine (Figure B) are not well-disposed and have serious side effects that can cause prompt indisposition in humans, such as central nervous system disorders, urinary tract disorders, hemopoiesis, porphyria, and extreme touchiness responses.…”
Section: Introductionmentioning
confidence: 99%
“…It is scientifically known that different pH values effect directly on the oxidation-reduction current peaks of FeII/FeIII ions in KCl as electrolyte on nano-sensors SiO 2 NPs/GCE [23]. The electrochemical analysis of FeII/FeIII ions in both acidic (pH = 2) and alkaline (pH = 12) is shown in Fig.…”
Section: Different Ph Studymentioning
confidence: 99%
“…Rao et al [12], using a diamond electrode with amperometric detection, found a high LOD of 0.05 µmol L −1 . Using carboxyl multiwalled carbon nanotubes to modify a glassy carbon electrode, the LOD of 0.032 µmol L −1 was determined by He et al [13]. Fotouhi et al [14] found a LOD of 6.1 µmol L −1 using a multiwalled nanotube film-coated glassy carbon electrode.…”
Section: Introductionmentioning
confidence: 99%